Communication Apprehension: Evaluation of Use of the Indonesian Language Version of the PRCA-24 [Kecemasan Komunikasi: Evaluasi Penggunaan PRCA-24 Versi Bahasa Indonesia] - Chelsea Tamara Aisyah; Lina Natalya; Edwin Adrianta Surijah; Linda Lee McCroskey (ANIMA Indonesian Psychological Journal, 2019)
Communication apprehension (CA) is the anxiety of an individual associated with actual or anticipated communication with others. The Personal Report of Communication Apprehension - 24 Items Version (PRCA-24) is a measurement implement constructed to measure the level of CA of an individual. This research was aimed at the evaluation of the use of the PRCA-24 within the context of research in Indonesia. The participants in the research comprised 336 undergraduate program university students, in an Indonesian university. The evaluation of this implement of measurement used, as an evidence source, validity, based upon internal consistency (analysis of the factors of exploration and reliability testing), and relatedness to another variable, i.e., assertiveness. Assertiveness was selected as the external variable, which predisposes people to communications apprehension behavior, and is measured using the Rathus Assertiveness Schedule (RAS). The results of the factor analysis and reliability testing indicated the dependability of the PRCA-24. This measurement implement also had positive and significant correlations with the variable of predisposition. This research produced implications for use of the PRCA-24 in a variety of different contexts, which will be further discussed in this paper. Communication apprehension (CA) adalah kecemasan individu yang berasosiasi dengan komunikasi yang nyata atau yang sedang diantisipasi terhadap orang lain. Personal Report of Communication Apprehension-24 items version (PRCA-24) adalah alat ukur yang dikonstruksikan untuk mengukur tingkat CA individu. Penelitian ini bertujuan mengevaluasi penggunaan PRCA-24 pada konteks penelitian di Indonesia. Partisipan penelitian adalah 336 mahasiswa program sarjana di suatu perguruan tinggi di Indonesia. Evaluasi alat ukur menggunakan sumber bukti validitas berdasarkan konsistensi internal (analisis faktor eksploratori dan pengujian reliabilitas), dan hubungan dengan variabel lain, yaitu asertivitas. Asertivitas dipilih sebagai variabel eksternal yang menjadi predisposisi perilaku CA dan diukur dengan menggunakan Rathus Assertiveness Schedule (RAS). Hasil analisis faktor dan pengujian reliabilitas menunjukkan kehandalan PRCA-24. Alat ukur ini juga berkorelasi positif dan signifikan dengan variabel predisposisi. Penelitian ini membawa implikasi berupa penggunaan PRCA-24 dalam berbagai konteks yang berbeda-beda yang akan dibahas lebih lanjut pada tulisan ini. Received 17 July 2019; Accepted 15 September 2019; Published 25 October 2019.